The Influence of Work Flexibility and Trust, and Transparency, on Employee Attachment of Creative Agency Companies in Jakarta: The Mediating Role of Organizational Commitment - Putri Larasati; Justine Tanuwijaya; Andreas Wahyu Gunawan (Dinasti International Journal of Education Management And Social Science, 2024)
The purpose of this study was to determine the effect of Flexibility and Trust, and Transparency on Organizational Commitment; to determine the effect of Organizational Commitment on Employee Engagement; and to determine Flexibility and Trust, Transparency on Employee Engagement through the mediating role of Organizational Commitment. This research uses a quantitative approach. The sample used is employees of agency companies in Jakarta. Researchers used data testing methods in this study including three main steps, namely Validity Test, Reliability Test and Model Feasibility Test. And the analysis method used in this study uses Structural Equation Modeling (SEM) analysis with software such as AMOS. The results of the study state that Flexibility and Trust have a positive influence on Employee Engagement, Flexibility and Trust have a positive influence on Organizational Commitment, Transparency has no positive effect on Employee engagement, Transparency has a positive effect on Organizational Commitment, Organizational Commitment has a positive effect on Employee engagement, Flexibility and Trust has a positive effect on Employee engagement through the mediating role of Organizational Commitment, Transparency has no positive effect on Employee engagement through the mediating role of Organizational Commitment.